Investigating The Effect of Nickel Buttering on Corrosion Resistance - Das, Santanu; Saha, Manas Kumar (Universitas Ahmad Dahlan, 2022)
Cladding is usually employed for improving corrosion and/or abrasion resistance of a component. Buttering layer between clad layer and structural steel is also sometimes provided to promote bonding between the cladding and the substrate. The buttering layer may also give desired corrosion resistance. Nickel is known to be a common austenite stabilizer, and it is often put inside cladding, coating, buttering, etc. to enhance hardness and corrosion protection of steel. In the current investigation, 316 austenitic stainless steel is deposited over nickel plated medium carbon steel substrate with the help of metal active gas welding. Nickel is accumulated on medium carbon steel by electroplating to act as a buttering layer. Welding current and torch travel speed, two important process parameters are varied with constant arc voltage to develop different values of heat input. Accelerated corrosion test in chloride atmosphere is done on ground and polished clad surface. Corrosion rate is observed to be decreased significantly for all the clad samples relative to the base material. However, no clear trend of corrosion rate against increment in heat input is found for reporting, but corrosion rate shows a typical pattern with the variation of heat input.